Гендерна асиметрія в сучасній українській державі - Краснопольська, Т. М.; Краснопольская, Т. М.; Krasnopol'skaja, Т. (My University, 2010)
The article discusses the concept of gender equality, its features in some areas of law, provides the main legal acts that ensure implementation of gender policy and gender equality, govern the conduct of gender analysis of legislation. Here we consider the prevailing gender asymmetry in Ukraine in the sphere of state management and proposes some ways of overcoming it.
Краснопольська Т. М. Гендерна асиметрія в сучасній українській державі / Т. М. Краснопольська // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 554-562.
Keywords: гендерна асиметрія; поняття принципів гендерної рівності; гендерна політика; гендерна експертиза законодавства; гендерна асиметрія в сфері державного управління; понятие принципа гендерного равенства; гендерная политика; гендерная экспертиза законодательства; гендерная асимметрия в сфере государственного управления; гендерная асимметрия; the concept of gender equality; gender Policy; gender expertise of legislation; gender asymmetry in public administration; gender asymmetry